Fundamental Rules Related to Determination an Applied Fundamental Study: Contemporary Medical Issues as an Example - Jaber, Saleh Mahmoud Saleh (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: This study dealt with the fundamental rules related to determination, and aims to explain the truth about the fundamental rules related to determination, a statement of the controls related to implementing the rules, and a statement inventory of the most important fundamental rules related to determination. Methods: the researcher adopted the descriptive approach, which appeared through describing images of contemporary issues and stating the overall meaning of the rules. The incomplete inductive approach was adopted by tracing the sayings, meanings, and contemporary issues that fall under the fundamentalist rules that were studied, where I collected the scientific material, then classified it, According to the principles of scientific research. Results: The study reached a number of results, the most prominent of which is that the reality of the fundamentalist rules related to determination is that it is a comprehensive issue that the fundamentalist follows in the general rulings he legislated from the beginning. It turned out that the fundamentalist rules related to determination have controls for their implementation that are necessary to work with, and the impact of the rules appeared clearly in a number of contimpirary medical applications. Conclusion: Highlighting the theoretical aspect in the contemporary medical application aspect in a number of medical applications, including: (treatment with drugs in the event of a legitimate alternative), (cloning stem cells for treatment), (not aborting a rape fetus in the first forty days), and (using anesthetics in necessary surgical operations).